Roche aims for 'slick, smart' Borders. (Bookseller, 2006)
The article reports that the three key factors in new Borders UK Ltd. chief executive David Roche' plan for the business include continued expansion, more support from publishers and supply chain efficiencies. Roche, who joined the U.S.-owned retailer three weeks ago, said he would work on the "establishment of a strategic route for Borders, combined with quick wins in making it a better run operation." Borders' international bookselling business turned a net profit of $5.6m in 2004/05 into a net loss of $7.8m in the year to January 28, 2006. Like-for-like superstore sales in the international segment were up by 0.4% for the year.